Chemical characteristics of spice paprika of different origins. (January 2018) - Molnár, Helga; Kónya, Éva; Zalán, Zsolt; Bata-Vidács, Ildikó; Tömösközi-Farkas, Rita; Székács, András; Adányi, Nóra
Abstract: Spice paprika powders from Bulgaria, China, Hungary, Peru, Serbia and Spain were examined to identify the most important differences in their major characteristics and to attempt to find chemical components revealing their origin. Bioactive components, contaminants, aroma and microbiological properties were determined: the amount of carotenoids, tocopherols, ascorbic acid and mycotoxins were determined by HPLC, flavoring properties by GC-MS, lead and cadmium content by atomic absorption spectrophotometry. Carotenoids were found at the highest concentration in samples from Peru and Spain and at the lowest, in Serbian samples. The concentrations of total tocopherol and ascorbic acid were found to be greater in samples from Hungary than from China. Aroma components characteristic to the location were detected in samples from each country of origin. The level of microbiological contamination was acceptable, while contaminants were found in Serbian, Spanish, Peruvian and Chinese samples. The effect of sample origin was also investigated using near infrared spectroscopy. Highlights: Spanish and Peruvian samples were notable for total carotenoids content. Ratio of capsanthin diesters to free capsanthins are proposed as indicators of origin. Aroma components characteristic to origin were detected in spice paprika samples. Based on NIR evaluation, some clustering occurred according the country of origin.